Challenge studies of human volunteers: ethical issues. Issue 1 (10th February 2004) - Hope, T; McMillan, J
Abstract : There is a long history of medical research that involves intentionally infecting healthy people in order to study diseases and their treatments. Such research—what might be called "human challenge studies"—are an important strand of much current research—for example, in the development of vaccinations. The many international and national guidelines about the proper conduct of medical research do not specifically address human challenge studies. In this paper we review the guidelines on the risk of harm that healthy volunteers may be exposed to in the course of medical research. We examine the ethical arguments that are implicit or explicit in these guidelines. We then ask whether there is reason for limiting such studies on grounds independent of risk of harm. We conclude that the major ethical concern with challenge studies is that of risk of harm and that the fact that a study is a challenge study is not a wrong in itself.